Corporate Social Responsibility Beyond Compliance: Effectiveness and Local Impact in Atsimo-Andrefana, Madagascar - Razafitahindraza Erica Feyzine Sulla; Rakotoniriana Noelisoa Jean Michel; Mandimbilaza Oscar Lucien (Yayasan Cendekia Citra Gemilang, 2026)
This study aims to analyze the effectiveness of Corporate Social Responsibility (CSR) in Atsimo-Andrefana, Madagascar, focusing on its evolution from voluntary practices into implicit obligations driven by social, institutional, and market pressures. Using a qualitative case study approach, 15 purposively selected informants, including company representatives, local communities, government officials, and civil society actors, were engaged through semi-structured interviews, observation, and document analysis, with triangulation and member checking ensuring credibility. The results show that CSR initiatives focus on education, health, infrastructure, and environmental management but are often sporadic, symbolic, and limited in impact. Stakeholder engagement is mostly consultative, and institutional constraints, such as weak governance and poor coordination, hinder sustained outcomes. Nevertheless, growing social expectations and reputational pressures are prompting companies to adopt more structured CSR practices, indicating a shift from soft law toward quasi-obligatory responsibilities with potential for meaningful local development.